Estrogenic Compounds: Chemical Characteristics, Detection Methods, Biological and Environmental Effects - Pamplona-Silva, Maria Tereza [UNESP] (2018)
Several chemical compounds are being studied for their capacities to cause imbalances in several biological systems. Some of those are able to affect the endocrine system and are known as endocrine disruptors. Many negative effects can be induced in the organisms by the action of these chemicals, highlighting the capacity to cause a decrease in the fertility rate, sex inversion, and problems in embryonic development and even cancer in humans. Those contaminants can be found in different environmental conditions, in groundwater, sediments, residual waters, sludges, and even in drinking water. The purpose of this review is to provide a general overview of the main estrogenic endocrine disruptors and their effects on living organisms, showing the most frequently used tools to detect these contaminants in environmental matrices. According to the data found, there is a need to develop more studies and improve the techniques, in order to effectively determine the mechanism of action of these contaminants and, thus, establish appropriate strategies for their removal from the environment and reduce their actions on living beings.